Pyrolysis mechanism of polyimide containing bio-molecule adenine building block. (May 2020) - Chen, Menghao; Liang, Bo; Guo, Yuhang; Li, Chengfeng; He, Xian; Hu, Jianghuai; Li, Renke; Zeng, Ke; Yang, Gang
Abstract: The pyrolysis mechanism and pyrolysis behavior of adenine-containing polyimide (API) were studied by thermogravimetric analyzer with Fourier transform infrared analysis and mass spectrometry (TG-FTIR-MS) and pyrolysis-gas chromatography-mass spectroscopy (Py-GC-MS). TG-FTIR-MS and Py-GC-MS were employed to continuously track the release of volatile products during the pyrolysis process. Thermogravimetric analysis (TG) indicated that API presented outstanding thermal stability. Additionally, it was observed that the volatile products were formed during the pyrolysis of API, including CO2, CO, HCN, benzonitrile, aniline and phenyl isocyanate. A probable pyrolysis mechanism of the API has been proposed according to the results of TG-FTIR-MS and Py-GC-MS. Highlights: The pyrolysis products and behavior of API were investigated via TG-FTIR-MS and Py-GC-MS. A obviously infrared absorption peak of HCN can be attributed to the pyrolysis of adenine. The API pyrolysis is roughly divided into three stages and a probable pyrolysis mechanism has been proposed.